TEKNIK INTERPRETASI DALAM TAFSIR AL QUR’AN DAN POTENSI DEVIASI PENERAPANNYA MENURUT ILMU DAKHIL - Afroni, Sihabbudin (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2018)
ABSTRACTThis paper describes the classification of interpretation, especially in terms of methods and techniques of interpretation. The methods and techniques that emerged in this study ofthe science of interpretation is very diverse and starting point on the tendency and interestof the scholar of the interpreter. Also presented are other factors of the emergence ofvarious methods and styles of interpretation known in the study of the science of Tafsir.Variations and differences of interpretation is a necessity but it does not mean the Qur'an isfree of interpretation. A mufassir must be bound by the rules of interpretation proposed bythe 'ulama. But sometimes carelessness of the mufassir in accepting secondary texts orother non-selective causes can potentially lead to irregularities and errors in interpretation.Ijtihad they are influenced by the ability of capability, linguistic knowledge, interest instudy, text references, flow affiliation, customs, methods and techniques of differentinterpretations make misinterpretation difficult to avoid. Erroneous interpretation is theobject of science research Dakhil. Globally the author introduces in this paper the Dakhilscience methodology. Writing this paper using a qualitative method approach that comesfrom various books relating to the above problems. The author attempts to explain hisanalysis exposively in order to explain or provide insight into the topics covered.ABSTRAK Makalah ini memaparkan klasifikasi tafsir terutama dari sisi metode dan teknikinterpretasi. Metode dan teknik yang muncul dalam penelitian ilmu tafsir ini sangatberagam dan bertitik tolak pada kecenderungan dan minat keilmuan sang penafsir.Dipaparkan pula faktor-faktor lain dari munculnya beragam metode dan corak tafsir yangdikenal dalam penelitian ilmu Tafsir. Variasi dan perbedaan tafsir adalah suatu keniscayaannamun bukan berarti Al-Qur‟an bebas tafsir. Seorang mufassir mesti terikat dengan kaidahkaidahpenafsiran yang dikemukakan ulama. Namun terkadang kecerobohan mufassirdalam menerima teks-teks sekunder atau sebab-sebab lain yang tidak selektif itulah yangdapat berpotensi menimbulkan penyimpangan dan kekeliruan dalam penafsiran. Ijtihadmereka dengan dipengaruhi oleh kemampuan daya tangkap, pengetahuan bahasa, minatkajian, referensi teks, afiliasi aliran, adat istiadat, metode dan teknik inetrpretasi yangberbeda menjadikan kekeliruan tafsir sulit untuk dihindari. Kekeliruan Tafsir inilah yangmenjadi objek penelitian ilmu Dakhil. Secara global penulis mengenalkan dalam makalahini metodologi ilmu Dakhil tersebut. Penulisan makalah ini menggunakan pendekatanmetode kualitatif yang bersumber dari berbagai buku yang berkaitan dengan permasalahandi atas. Penulis berupaya menjelaskan analisisnya secara eksposisi dengan tujuan untukmenjelaskan atau memberikan pengertian topik yang dibahas. Keywords: Tafseer Classification, Interpretation Method, Interpretation Technique,Technique, Linguistics, Systemic, Socio Historical, Science Dakhil.